Structural validation of The Patient Health Questionnaire-9 (PHQ-9) among Filipina and Indonesian female migrant domestic workers in Macao: STRUCTURAL VALIDATION OF PHQ-9. (January 2021) - Hall, Brian J.; Patel, Anushka; Lao, Lorris; Liem, Andrian; Mayawati, Elisabeth H.; Tjipto, Susana
Highlights: The factorial validity and multi-group invariance of the PHQ-9 was evaluated The best fitting was a 2-factor model with cognitive/affective and somatic factors Multi-group measurement invariance was demonstrated for the 2-factor model Abstract: Within diverse global populations, validated tools are needed to assess common mental disorders. The Patient Health Questionnaire-9 (PHQ-9) is one of the most commonly used depression screeners. However, the PHQ-9 has not been structurally validated among female migrant domestic workers (MDWs). Female MDWs constitute a population numbering 11.5 million, and commonly report depression. This study aimed to structurally validate the PHQ-9 among Filipina and Indonesian female MDWs in Macao Special Administrative Region of China. Participants were recruited using respondent driven sampling. Participants were adult female MDWs from The Philippines ( N =1375) or Indonesia ( N =367) and legally working in Macao. We used confirmatory factor analysis (CFA) to test five structural models of depression using all PHQ-9 items with the Filipina and Indonesian samples. We applied multi-group CFA to test measurement invariance across samples. A two-factor (cognitive/affective, somatic) model yielded the best fit within both samples, and the multi-group CFA demonstrated invariance across samples. The two-factor model best represents the factor structure of the PHQ-9 among Filipina and Indonesian female MDWs.